A binder and a method for preparing the same, a ceramic-coated separator, and a battery

CN122917705APending Publication Date: 2026-10-16JIANGSU ADVANCED MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611132211.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]传统陶瓷隔膜所用的粘结剂通常为亲水性过强的水性粘结剂(如PAA、PAM等),在干燥过程中,浆料中的水分难以被彻底脱除,残留水分高

Benefits of technology

本申请提供的粘结剂,具有最低临界溶解温度 (LCST) 特性,在LCST以下(如室温浆料制备阶段),该粘结剂能够表现出良好的亲水性,分子链舒展,可稳定分散陶瓷颗粒(如氧化铝、勃姆石),形成均匀、稳定的水性涂布浆料。在涂布后烘干过程中,当温度跨越LCST时,聚合物-水间的氢键作用急剧减弱,聚合物链的疏水相互作用增强。聚合物链发生脱水、构象塌缩并相互聚集,从水中析出,实现热致相分离。相分离后,聚合物相形成致密的粘接网络,将陶瓷颗粒牢固粘结,同时将大部分水分“排挤”出去,形成易于蒸发的游离水。这极大地提高了水分脱除的动力学和彻底性,使得最终获得的涂层内部孔隙率高且水分残留极低,从而可有效改善涂层干燥均匀性,降低干燥收缩应力,从而减轻或避免隔膜卷边,进而有利于提高电池的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917705A_ABST
    Figure CN122917705A_ABST
Patent Text Reader

Abstract

The application discloses a kind of binder and its preparation method, ceramic coating diaphragm and battery, belong to battery material technical field. According to mole percentage, binder is obtained by the monomer composition including 20%~49.5% hydrophilic monomer A, 48%~78% temperature-sensitive monomer B and 2%~2.5% crosslinking monomer C reaction;LCST of binder in aqueous solution is 40 DEG C~80 DEG C.The binder shows good hydrophilicity below LCST, can stably disperse ceramic particles, form uniform and stable slurry;When temperature crosses LCST, polymer chain occurs dehydration, conformation collapse and mutual aggregation, and is precipitated from water;Polymer phase forms dense bonding network, firmly bonds ceramic particles, simultaneously " expels " most water, so that coating internal porosity is high and water residue is extremely low, it is favorable to improve coating drying uniformity, reduce drying shrinkage stress, reduce or avoid diaphragm edge curling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials technology, and more specifically, to a binder and its preparation method, a ceramic-coated separator, and a battery. Background Technology

[0002] Traditional ceramic separators typically use water-based binders with excessive hydrophilicity (such as PAA and PAM). During the drying process, it is difficult to completely remove moisture from the slurry, resulting in high residual moisture. When high-moisture separators are used in battery cells, moisture easily reacts with the electrolyte (such as LiPF6), producing corrosive gases and substances such as HF, causing cell swelling. Furthermore, the generated HF corrodes highly active high-nickel ternary cathode materials (such as NCM811 and NCA), causing transition metal dissolution, damaging the CEI / SEI film, and leading to reduced initial charge / discharge efficiency and capacity decay. In addition, continuous side reactions consume active lithium and electrolyte, accelerating battery performance degradation and shortening the battery's cycle life.

[0003] Therefore, this application is hereby submitted. Summary of the Invention

[0004] The purpose of this application includes providing an adhesive and its preparation method, a ceramic-coated separator, and a battery to solve or improve the above-mentioned technical problems.

[0005] This application can be implemented as follows: In a first aspect, this application provides an adhesive, which, by molar percentage, is obtained by reacting a monomer composition comprising 20% ​​to 49.5% hydrophilic monomer A, 48% to 78% thermosensitive monomer B, and 2% to 2.5% crosslinking monomer C. The lowest critical dissolution temperature (LCST) of the binder in aqueous solution is 40℃~80℃.

[0006] In an optional embodiment, the weight-average molecular weight of the adhesive is 200 kDa to 400 kDa; and / or, the molecular weight multiple distribution index (PDI) of the adhesive is 1.25 to 2.5.

[0007] In an optional embodiment, the hydrophilic monomer A includes at least one of acrylic acid, ethyl acrylate, acrylamide, N-hydroxymethylacrylamide, hydroxyethyl methacrylate, and polyethylene glycol methacrylate. And / or, the thermosensitive monomer B includes at least one of N-isopropylacrylamide, N-vinylcaprolactam, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, poly(propylene oxide), and poly(ethylene oxide-propylene oxide) blocks; And / or, the crosslinking monomer C includes at least one of N,N'-methylenebisacrylamide, divinylbenzene, and ethylene glycol dimethacrylate.

[0008] In an optional embodiment, the adhesive is obtained from a block copolymer and a crosslinking monomer C through a crosslinking reaction, wherein the block copolymer has the general structural formula A. x B y The molar ratio of the crosslinking monomer C to the total molar ratio of the hydrophilic monomer A and the thermosensitive monomer B used to form the block copolymer is 1:39 to 1:49; wherein, A x Block A of the polymer represents a number-average degree of polymerization of x; Block B y The number-average degree of polymerization of a polymer B block is represented by y; x and y are independent integers in the range of 20 to 50.

[0009] In an optional embodiment, the block copolymer has 1 to 2 glass transition temperatures.

[0010] Secondly, this application provides a method for preparing an adhesive as described in any of the foregoing embodiments, wherein the adhesive is prepared by free radical polymerization or controlled free radical polymerization.

[0011] In an optional embodiment, the preparation of the adhesive includes: preparing an aqueous solution of hydrophilic monomer A, thermosensitive monomer B, crosslinking monomer C and an initiator; adding a portion of the aqueous solution to a reaction vessel and reacting until the solution viscosity increases; and adding the remaining aqueous solution to the reaction vessel and reacting.

[0012] In an optional embodiment, the initiator includes at least one of sodium persulfate, ammonium persulfate, and potassium persulfate.

[0013] In an optional embodiment, the amount of initiator is 1% to 2% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0014] In an optional embodiment, the preparation of the adhesive includes: preparing a hydrophilic monomer A into an aqueous solution of monomer A, and preparing a thermosensitive monomer B and a crosslinking monomer C into aqueous solutions of monomer B and monomer C, respectively. A mixture of monomer A aqueous solution, chain transfer agent, and initiator is added to a reaction vessel and reacted until the solution viscosity increases. A monomer B aqueous solution is added to the reaction vessel and reacted, followed by the addition of monomer C aqueous solution and reaction. A chain transfer cleavage agent is then added for cleavage. Alternatively, a portion of monomer A aqueous solution is mixed with a chain transfer agent and an initiator and added to a reaction vessel to react until the solution viscosity increases; a portion of monomer B aqueous solution is added to the reaction vessel and reacted, then a portion of monomer C aqueous solution is added and reacted to form a first multiblock copolymer; in the same manner, a portion of monomer A aqueous solution is added to the first multiblock copolymer and reacted, then a portion of monomer B aqueous solution is added and reacted, then a portion of monomer C aqueous solution is added and reacted, and so on, repeated multiple times, and a chain transfer cleavage agent is added for cleavage.

[0015] In an optional embodiment, the amount of chain transfer agent added is 0.5% to 1.5% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0016] In an optional embodiment, the chain transfer agent includes at least one of dithioesters, trithiocarbonates, and xanthate compounds.

[0017] In an optional embodiment, the dithioesters include at least one of benzyl dithiobenzoate, S-(thiobenzoyl)thioacetic acid, and 2-cyanopropyl-2-yl dithiobenzoate.

[0018] And / or, trithiocarbonates include at least one of 2-(dodecylthiothiocarbonylthio)-2-methylpropionic acid and 4-cyano-4-(dodecylthioalkylthiocarbonyl)thioalkylpentanoic acid; And / or, xanthate compounds include O-ethyl-S-(3-oxobut-2-yl)dithiocarbonate.

[0019] In an optional embodiment, the amount of initiator is 0.5% to 2% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0020] In an optional embodiment, the initiator includes at least one of sodium persulfate, ammonium persulfate, and potassium persulfate.

[0021] Thirdly, this application provides a ceramic-coated diaphragm, including a base film and an inorganic ceramic coating layer disposed on at least one side surface of the base film; the inorganic ceramic coating layer contains an adhesive of any of the aforementioned embodiments.

[0022] In an optional embodiment, the surface and / or interior of the inorganic ceramic coating layer have pores, wherein the effective area is 0.8 μm. 2 ~10μm 2 The number of holes is between 20 and 50.

[0023] In an optional embodiment, the ceramic-coated diaphragm further contains inorganic ceramic particles, and the mass of the binder is 5% to 20% of the mass of the inorganic ceramic particles, more preferably 5% to 15%.

[0024] Fourthly, this application provides a battery including the ceramic-coated separator of the aforementioned embodiments.

[0025] In an optional embodiment, the thickness of the ceramic-coated diaphragm is 1 μm to 5 μm.

[0026] The beneficial effects of this application include: The binder provided in this application possesses a minimum critical solution temperature (LCST) characteristic. Below the LCST (such as during room temperature slurry preparation), this binder exhibits excellent hydrophilicity, with extended molecular chains, enabling stable dispersion of ceramic particles (such as alumina and boehmite) to form a uniform and stable aqueous coating slurry. During the drying process after coating, when the temperature exceeds the LCST, the hydrogen bonding between the polymer and water weakens sharply, while the hydrophobic interactions of the polymer chains strengthen. The polymer chains undergo dehydration, conformational collapse, and aggregation, precipitating from the water and achieving thermally induced phase separation. After phase separation, the polymer phase forms a dense adhesive network that firmly binds the ceramic particles while simultaneously "squeezing out" most of the water, forming easily evaporable free water. This significantly improves the kinetics and thoroughness of water removal, resulting in a coating with high internal porosity and extremely low residual moisture. This effectively improves the coating drying uniformity, reduces drying shrinkage stress, thereby mitigating or preventing separator edge curling, and ultimately enhancing the electrochemical performance of the battery. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a SEM image of the ceramic-coated diaphragm prepared in Example 1. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0030] The following provides a detailed description of the binder and its preparation method, the ceramic-coated separator, and the battery provided in this application.

[0031] This application provides an adhesive, in molar percentage, obtained by reacting a monomer composition comprising 20% ​​to 49.5% hydrophilic monomer A, 48% to 78% thermosensitive monomer B, and 2% to 2.5% crosslinking monomer C. The LCST of this adhesive in aqueous solution is 40℃~80℃.

[0032] The binder provided in this application possesses a minimum critical solution temperature (LCST) characteristic, which refers to the critical temperature at which phase separation occurs in the polymer solution. When the ambient temperature is below the LCST, the binder dissolves in water. Once the ambient temperature rises above the LCST, the temperature increase weakens the polar / hydrogen bonding interactions between the polymer and the solvent (water), while simultaneously enhancing the hydrophobic interactions within the polymer and the entropy increase driving force of the entire system. This leads to the binder transitioning from a dissolved state to a phase-separated state; that is, the polymer chains of the binder collapse, aggregate, and precipitate from the water, resulting in phase separation. It should be noted that the binder undergoes a phase transition in aqueous solution as the temperature rises to the threshold, and the LCST is reversible in aqueous solution after cooling. However, it does not possess an LCST in electrolytes and therefore does not dissolve in electrolytes. After the binder precipitates from the water and undergoes phase separation, the polymer phase forms a dense adhesive network that firmly binds the ceramic particles while "squeezing out" most of the water. This results in a coating with high internal porosity and extremely low residual moisture, which helps improve the coating's drying uniformity, reduce drying shrinkage stress, and alleviate or prevent membrane curling, thereby improving the battery's electrochemical performance.

[0033] In some alternative embodiments, the molar percentage of hydrophilic monomer A can be 20%, 25%, 30%, 35%, 40%, 45%, or 49.5%, or other values ​​within the range of 20% to 49.5%.

[0034] The molar percentage of thermosensitive monomer B can be 48%, 50%, 55%, 60%, 65%, 70%, 75% or 78%, or other values ​​within the range of 48% to 78%.

[0035] The molar percentage of the crosslinking monomer C can be 2%, 2.1%, 2.2%, 2.3%, 2.4%, or 2.5%, or other values ​​within the range of 2% to 2.5%.

[0036] If the molar percentage of thermosensitive monomer B is less than 48%, the thermosensitive properties of the adhesive will be not obvious and the phase change driving force will be insufficient; if the molar percentage of thermosensitive monomer B is greater than 78%, the hydrophilicity of the adhesive will be reduced and the bonding performance will be lower.

[0037] In some alternative embodiments, the LCST of the adhesive in the aqueous solution can be 40°C to 80°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, or other values ​​within the range of 40°C to 80°C.

[0038] This application achieves an LCST (lower limit temperature) of 40°C to 80°C in aqueous solution by controlling the molar ratio of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C within the aforementioned range. Furthermore, the LCST behavior of the binder is also influenced by molecular weight, molecular weight distribution, and molecular chain configuration.

[0039] In some alternative embodiments, the weight-average molecular weight of the adhesive can be 200kDa to 400kDa, such as 200kDa, 250kDa, 300kDa, 350kDa or 400kDa, or other values ​​in the range of 200kDa to 400kDa.

[0040] If the weight-average molecular weight of the adhesive is too low, the adhesive performance and LCST characteristics of the adhesive will be not obvious; if the weight-average molecular weight of the adhesive is too high, the LCST characteristics of the adhesive will be significant, the LCST temperature will be raised, there will be no LCST characteristics during the drying process, and it will be difficult to achieve the low moisture effect in the end.

[0041] In this application, the polymer polydispersity index (PDI) is the ratio of weight-average molecular weight to number-average molecular weight (Mw / Mn), used to characterize the breadth of the polymer molecular weight distribution. In some optional embodiments, the PDI of the binder can be 1.25 to 2.5, such as 1.25, 1.5, 1.75, 2.0, 2.25, or 2.5, or other values ​​within the range of 1.25 to 2.5.

[0042] A higher PDI value indicates a wider molecular weight distribution and greater differences in molecular chain lengths within the sample. When the polymer polydispersity index (PDI) of the binder is relatively narrow, the corresponding LCST characteristics are more pronounced, resulting in better subsequent moisture control of the membrane.

[0043] In this application, hydrophilic monomer A is mainly used to ensure the water solubility and slurry stability of the binder at low temperatures and to enhance its hydrophilicity. It can introduce stronger or more hydrogen bond donors / acceptors into the binder. Thermosensitive monomer B is mainly used to provide LCST properties. Crosslinking monomer C can undergo slight crosslinking during the reaction process, which is beneficial to improving the mechanical strength and electrolyte resistance of the coating.

[0044] In some alternative embodiments, hydrophilic monomer A may, by way of example but not limitation, include at least one of acrylic acid, ethyl acrylate, acrylamide, N-hydroxymethylacrylamide, hydroxyethyl methacrylate, and polyethylene glycol methacrylate.

[0045] Thermosensitive monomer B may, by way of example but not limitation, include at least one of N-isopropylacrylamide, N-vinylcaprolactam, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, poly(propylene oxide), and poly(ethylene oxide-propylene oxide) blocks.

[0046] Crosslinking monomer C may, by way of example but not limitation, include at least one of N,N'-methylenebisacrylamide, divinylbenzene and ethylene glycol dimethacrylate.

[0047] In this application, the binder can be a cross-linked block copolymer or a cross-linked random copolymer. Since the number of continuous identical structural units in a cross-linked random copolymer is small, the LCST characteristic is not significant and the effect is not as controllable as that of a cross-linked block copolymer. Therefore, in some preferred embodiments, the binder is a cross-linked block copolymer.

[0048] The aforementioned "crosslinked block copolymer" is obtained by first preparing a block copolymer and then performing crosslinking. In some optional embodiments, the crosslinked block copolymer is obtained from a block copolymer and a crosslinking monomer C through a crosslinking reaction, and the general structural formula of the block copolymer is A. x B y The molar ratio of the crosslinking monomer C to the total molar ratio of the hydrophilic monomer A and the thermosensitive monomer B used to form the block copolymer is 1:39 to 1:49; wherein, A x Block A of the polymer represents a number-average degree of polymerization of x; Block B y The number-average degree of polymerization of a polymer B block is represented by y; x and y are independent integers in the range of 20 to 50.

[0049] In some alternative embodiments, the block copolymers described above have 1 to 2 glass transition temperatures.

[0050] Accordingly, this application also provides a method for preparing the above-mentioned adhesive. When the adhesive is a cross-linked random copolymer, the adhesive is prepared by free radical polymerization; when the adhesive is a cross-linked block copolymer, the adhesive is prepared by controlled free radical polymerization (such as RAFT or ATRP) or free radical polymerization.

[0051] In some alternative embodiments, when the binder is a cross-linked block copolymer, the binder is prepared by controlled free radical polymerization, which, compared to free radical polymerization, can give the binder the advantages of a narrower molecular weight distribution and better performance stability.

[0052] For example, the preparation of crosslinked random copolymers may include: preparing an aqueous solution of hydrophilic monomer A, thermosensitive monomer B, crosslinking monomer C and an initiator; adding a portion of the aqueous solution to a reaction vessel and reacting until the solution viscosity increases; and adding the remaining aqueous solution to the reaction vessel and reacting.

[0053] For example, the hydrophilic monomer A, the thermosensitive monomer B, the crosslinking monomer C, and the initiator can be prepared into an aqueous solution with a solid content of 10% to 30%; 10% to 20% of the aqueous solution by mass is added to the reaction vessel and reacted at 60°C to 70°C until the solution viscosity increases; the remaining aqueous solution is added to the reaction vessel and the temperature is raised to 75°C to 85°C and reacted for 1.5 to 2.5 hours.

[0054] The initiator may, by way of example but not by way of limitation, include at least one of sodium persulfate, ammonium persulfate and potassium persulfate.

[0055] The amount of initiator can be 1% to 2% of the total mass of hydrophilic monomer A, thermosensitive monomer B and crosslinking monomer C, such as 1%, 1.5% or 2%, or other values ​​within the range of 1% to 2%.

[0056] In some alternative embodiments, the preparation of the crosslinked block copolymer may include: preparing a hydrophilic monomer A into an aqueous solution of monomer A, and preparing a thermosensitive monomer B and a crosslinking monomer C into aqueous solutions of monomer B and monomer C, respectively. The aqueous solution of monomer A is mixed with the chain transfer agent and the initiator and then added to the reaction vessel to react until the solution viscosity increases. The aqueous solution of monomer B is added to the reaction vessel and reacted, followed by the aqueous solution of monomer C and reacted. Then, the chain transfer cleavage agent is added to perform cleavage.

[0057] Alternatively, a portion of the aqueous solution of monomer A is mixed with a chain transfer agent and an initiator and added to a reaction vessel to react until the solution viscosity increases; a portion of the aqueous solution of monomer B is added to the reaction vessel and reacted, then a portion of the aqueous solution of monomer C is added and reacted to form a first multiblock copolymer; in the same manner, a portion of the aqueous solution of monomer A is added to the first multiblock copolymer and reacted, then a portion of the aqueous solution of monomer B is added and reacted, then a portion of the aqueous solution of monomer C is added and reacted, and so on, repeated multiple times, and a chain transfer agent is added for chain cleavage.

[0058] In the second approach, hydrophilic monomer A can be prepared as an aqueous solution with a solid content of 20%–40%. Thermosensitive monomer B and crosslinking monomer C can be prepared as aqueous solutions with solid contents of 20%–40%, respectively. 20%–40% by mass of the monomer A aqueous solution is mixed with a chain transfer agent and an initiator and added to a reaction vessel, reacting at 60°C–70°C until the solution viscosity increases. Then, 20%–40% by mass of the monomer B and monomer C aqueous solutions are added to the reaction vessel and reacted to form a first multi-block copolymer. Following the same method, monomer A aqueous solution is added to the first multi-block copolymer and reacted at 60°C–70°C until the solution viscosity increases. Then, a portion of the monomer B aqueous solution is added and reacted, followed by the addition of monomer C aqueous solution and reaction. This process is repeated multiple times, with the addition of a chain transfer cleavage agent for cleavage. Preferably, the number of repetitions does not exceed 5 times. Increasing the number of repetitions in block copolymerization is equivalent to reducing the number of monomers in each block unit. The LCST property is positively correlated with the number of monomers in the temperature-sensitive block unit. Increasing the number of repetitions will lead to a decrease in the number of temperature-sensitive block units, which may result in the adhesive not having the LCST property.

[0059] The chain transfer agent may, by way of example but not by way of limitation, include at least one of dithioesters, trithiocarbonates and xanthate compounds.

[0060] Dithioesters may, by way of example but not by way of limitation, include at least one of benzyl dithiobenzoate, S-(thiobenzoyl)thioacetic acid and 2-cyanopropyl-2-dithiobenzoate; Trithiocarbonates may, by way of example but not by way of limitation, include at least one of 2-(dodecylthiothiocarbonylthio)-2-methylpropionic acid and 4-cyano-4-(dodecylthiocarbonylthio)thiopentanoic acid.

[0061] Xanthate compounds may include, by way of example but not by way of limitation, O-ethyl-S-(3-oxobut-2-yl)dithiocarbonate.

[0062] In some alternative embodiments, the amount of chain transfer agent added can be 0.5% to 1.5% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C, such as 0.5%, 0.8%, 1%, 1.2%, or 1.5%, or other values ​​within the range of 0.5% to 1.5%.

[0063] The amount of chain transfer agent added can adjust the molecular weight of the binder. The higher the molecular weight of the binder, the more significant its LCST characteristics. If the molecular weight is too low, the binder will not have LCST characteristics.

[0064] In some alternative embodiments, the initiator used in the preparation of the crosslinked block copolymer may also include at least one of sodium persulfate, ammonium persulfate, and potassium persulfate. The amount of initiator may be 0.5% to 2% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C, such as 0.5%, 1%, 1.5%, or 2%, or other values ​​within the range of 0.5% to 2%.

[0065] In addition, this application also provides a ceramic-coated diaphragm, which includes a base membrane and an inorganic ceramic coating layer disposed on at least one side surface of the base membrane; the inorganic ceramic coating layer contains the aforementioned binder.

[0066] In optional embodiments, the ceramic-coated diaphragm further contains inorganic ceramic particles, and the mass of the binder solution is 5% to 20% of the mass of the inorganic ceramic particles, such as 5%, 10%, 15%, or 20%, or other values ​​within the range of 5% to 20%. In some preferred embodiments, the mass of the binder solution is 5% to 15% of the mass of the inorganic ceramic particles. The solid content of the binder solution is 15% to 25%.

[0067] If the mass of the binder is less than 5% of the mass of the inorganic ceramic particles, it is difficult to provide sufficient bonding force; if the mass of the binder is more than 20% of the mass of the inorganic ceramic particles, it is easy to cause the slurry viscosity to be too high, which is not conducive to coating. In addition, when the mass of the binder is in the range of 15% to 20% of the mass of the inorganic ceramic particles, although it improves the moisture content of the diaphragm, it is easy to cause the thermal shrinkage performance of the diaphragm to deteriorate; therefore, the range of 5% to 15% is preferred.

[0068] In an optional embodiment, the ceramic-coated diaphragm further contains a wetting agent, the mass of which can be 0.1% to 0.5% of the mass of the inorganic ceramic particles, such as 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%, or other values ​​within the range of 0.1% to 0.5%. The wetting agent may include, for example, sodium dodecyl sulfate.

[0069] In an optional embodiment, the ceramic-coated diaphragm further contains a dispersant, the mass of which can be 0.1% to 0.5% of the mass of the inorganic ceramic particles, such as 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%, or other values ​​within the range of 0.1% to 0.5%. The dispersant may include sodium polyacrylate, etc.

[0070] In an optional embodiment, the ceramic-coated diaphragm further contains a thickener, the mass of which can be 0.2% to 0.3% of the mass of the inorganic ceramic particles, such as 0.2%, 0.25%, or 0.3%, or other values ​​within the range of 0.2% to 0.3%. The thickener may include sodium carboxymethyl cellulose, etc.

[0071] In an optional embodiment, the surface and / or interior of the inorganic ceramic coating layer have pores, wherein the effective area is 0.8 μm. 2 ~10μm 2 The number of holes is between 20 and 50. The aforementioned "effective area" refers to the equivalent circular area corresponding to the surface holes of the inorganic ceramic coating.

[0072] The aforementioned pores are formed when the adhesive reaches LCST behavior during the drying and heating process, undergoing a phase transition to form particle agglomerates, which then shrink in volume as drying continues. The pore area is affected by the size of the particle agglomerates. SEM observation of the pore interior reveals the presence of polymer agglomerates, and EDS analysis confirms the presence of nitrogen (N).

[0073] The presence of these pores can improve the gas permeability and ion conduction performance of the separator, thereby enhancing the fast-charging performance of the battery. If the effective area of ​​the pores is less than 0.8 μm... 2 The voids may be due to the accumulation of ceramic structures in the coating, which have limited effect on improving the membrane's air permeability; if the effective area of ​​the pores is greater than 10 μm... 2 Insufficient wetting during the coating process leads to this; if the effective area of ​​the pores is greater than 0.8μm. 2 Furthermore, an excessive number of them will worsen the heat resistance and reduce the needle-punching strength of the diaphragm.

[0074] In some alternative embodiments, the peel strength of the ceramic-coated diaphragm is 84 N / m to 165 N / m.

[0075] In some alternative embodiments, the moisture content of the ceramic-coated diaphragm does not exceed 1150 ppm.

[0076] In some alternative embodiments, the air permeability of the ceramic-coated diaphragm is 65s / 100cc to 120s / 100cc.

[0077] In some alternative embodiments, the ceramic-coated diaphragm exhibits a heat shrinkage of 1.1% to 4.2% at 150°C.

[0078] In addition, this application also provides a battery including the above-mentioned ceramic-coated separator.

[0079] In an optional embodiment, the thickness of the ceramic-coated diaphragm can be 1μm to 5μm, such as 1μm, 2μm, 3μm, 4μm or 5μm, or other values ​​within the range of 1μm to 5μm.

[0080] The features and performance of this application will be further described in detail below with reference to the embodiments.

[0081] Example 1 This embodiment provides a ceramic-coated diaphragm, which uses a multi-channel micro-grooving method to coat a ceramic slurry onto the surface of a base membrane and then dries it in an oven at 80°C to obtain an inorganic ceramic coating layer with a thickness of 2μm.

[0082] The preparation of the ceramic slurry includes: adding deionized water to a mixing tank, followed by adding 0.2 parts of wetting agent (sodium dodecyl sulfate), 0.2 parts of thickener (sodium carboxymethyl cellulose), 100 parts of inorganic ceramic particles (alumina), and 10 parts of binder solution (solid content of 20%), stirring at high speed, and finally adding 0.5 parts of dispersant (sodium polyacrylate) to adjust the dynamic surface tension of the slurry to obtain a uniform and stable ceramic slurry.

[0083] The above-mentioned adhesive is a cross-linked block copolymer, which is prepared by controlled free radical polymerization, specifically including the following steps: The materials were prepared with the following molar percentages: hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C, respectively: 20%, 78%, and 2%. Hydrophilic monomer A (acrylamide) was prepared into an aqueous solution with a solid content of 20%, and the aqueous solution of monomer A was divided into three equal parts; thermosensitive monomer B (N-isopropylacrylamide) and crosslinking monomer C (N,N'-methylenebisacrylamide) were prepared into aqueous solutions with a solid content of 20% respectively, and were also divided into three equal parts respectively.

[0084] Take a portion of the aqueous solution of monomer A and mix it with 1% of the total mass of all monomers, a chain transfer agent (benzyl dithiobenzoate), and 0.5% of the total mass of all monomers, an initiator (ammonium persulfate). Add the mixture to a reactor and react at 65°C until the solution viscosity increases, then react for 30 minutes. Next, take a portion of the aqueous solution of monomer B and add it dropwise to the reactor. After the addition is complete, react for 60 minutes. Then, take a portion of the aqueous solution of monomer C and add it to the reactor and react for 60 minutes. Following the above order of addition, add the remaining two portions of aqueous solutions of monomer A, monomer B, and monomer C in sequence and react for 60 minutes each. Finally, add the chain transfer agent to remove the chain transfer.

[0085] That is, during the entire reaction process, the aqueous solutions of monomer A, monomer B, and monomer C are added in three separate portions.

[0086] The SEM image of the inorganic ceramic coating layer prepared in this embodiment is shown below. Figure 1 As shown, by Figure 1 As can be seen, the inorganic ceramic coating contains pores (as shown in the red area). SEM observation of the interior of the pores reveals polymer agglomerates, and EDS analysis of the polymer agglomerates reveals the presence of nitrogen.

[0087] Example 2 The difference between this embodiment and Example 1 is that the molar percentages of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C are 49.5%, 48.5%, and 2%, respectively.

[0088] Example 3 The difference between this embodiment and Example 1 is that the molar percentages of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C are 35%, 63%, and 2%, respectively.

[0089] Example 4 The difference between this embodiment and Embodiment 3 is that the aqueous solutions of monomer A, monomer B, and monomer C are added in five separate portions throughout the entire reaction process.

[0090] Example 5 The difference between this embodiment and Embodiment 3 is that the aqueous solutions of monomer A, monomer B, and monomer C are added only once during the entire reaction process.

[0091] Example 6 The difference between this embodiment and Embodiment 3 is that: hydrophilic monomer A is ethyl acrylate, thermosensitive monomer B is N-vinylcaprolactam, and crosslinking monomer C is ethylene glycol dimethacrylate.

[0092] Example 7 The difference between this embodiment and Embodiment 3 is that the amount of chain transfer agent added is 1.5% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0093] Example 8 The difference between this embodiment and Embodiment 3 is that the amount of chain transfer agent added is 0.5% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0094] Example 9 The difference between this embodiment and Embodiment 3 is that the number of binders in the ceramic slurry is 5 parts.

[0095] Example 10 The difference between this embodiment and Embodiment 3 is that the number of binders in the ceramic slurry is 15 parts.

[0096] Example 11 The difference between this embodiment and Embodiment 3 is that the number of binders in the ceramic slurry is 20 parts.

[0097] Example 12 This embodiment provides a ceramic-coated diaphragm, which uses a multi-channel micro-grooving method to coat a ceramic slurry onto the surface of a base membrane and then dries it in an oven at 80°C to obtain an inorganic ceramic coating layer with a thickness of 2μm.

[0098] The preparation of the ceramic slurry includes: adding deionized water to a mixing tank, followed by adding 0.2 parts of wetting agent (sodium dodecyl sulfate), 0.3 parts of thickener (sodium carboxymethyl cellulose), 100 parts of inorganic ceramic particles (alumina), and 10 parts of binder solution (solid content of 20%) in sequence, stirring at high speed, and finally adding 0.5 parts of dispersant (sodium polyacrylate) to adjust the dynamic surface tension of the slurry to obtain a uniform and stable ceramic slurry.

[0099] The above-mentioned adhesive is a cross-linked random copolymer, which is prepared by free radical polymerization, specifically including the following steps: The materials were prepared with the following molar percentages: hydrophilic monomer A (acrylamide), thermosensitive monomer B (N-isopropylacrylamide), and crosslinking monomer C (N,N'-methylenebisacrylamide), respectively: 20%, 78%, and 2%.

[0100] The hydrophilic monomer A, thermosensitive monomer B, crosslinking monomer C, and 1% (by mass) of initiator (ammonium persulfate) of the total monomers were dissolved in deionized water to prepare an aqueous solution with a solid content of 20%. 10% of this aqueous solution was added to the reactor as a base, and the reaction temperature was set at 65°C. The reaction proceeded until the solution viscosity increased. The remaining aqueous solution was then added dropwise to the reactor. After the addition was complete, the temperature was raised to 80°C, and the reaction was allowed to proceed for 2 hours.

[0101] Comparative Example 1 The difference between this comparative example and Example 3 is that, by molar percentage, the binder is obtained by reacting 98% of hydrophilic monomer A (acrylamide) and 2% of crosslinking monomer C (ethylene glycol dimethacrylate).

[0102] Comparative Example 2 The difference between this comparative example and Example 3 is that the aqueous solutions of monomer A, monomer B, and monomer C were added in eight separate batches throughout the reaction process.

[0103] Comparative Example 3 The difference between this comparative example and Example 3 is that the molar percentages of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C are 10%, 88%, and 2%, respectively.

[0104] Comparative Example 4 The difference between this comparative example and Example 3 is that the molar percentages of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C are 70%, 28%, and 2%, respectively.

[0105] Comparative Example 5 The difference between this comparative example and Example 3 is that the amount of chain transfer agent added is 3% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0106] Comparative Example 6 The difference between this comparative example and Example 3 is that the amount of chain transfer agent added is 0.2% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C.

[0107] Comparative Example 7 The difference between this comparative example and Example 3 is that the number of parts of the binder solution in the ceramic slurry is 2.

[0108] Comparative Example 8 The difference between this comparative example and Example 3 is that the number of parts of binder solution in the ceramic slurry is 25 parts.

[0109] Test case The ceramic-coated diaphragms prepared in Examples 1-12 and Comparative Examples 1-8 were subjected to performance tests, and the test methods are as follows: (1) Turbidity method: Prepare a low-concentration (e.g., 1 mg / mL) polymer aqueous solution, slowly heat it in a temperature control device, and monitor the transmittance at a wavelength of 500 nm to 600 nm using a UV-Vis spectrophotometer. The temperature at which the transmittance drops sharply by 50% is the LCST.

[0110] (2) Glass transition temperature Tg: determined by differential scanner DSC3 (Mettler).

[0111] (3) Weight-average molecular weight and its distribution PDI: A mobile phase of 0.1 mol / L NaNO3 and 0.02 mol / L NaN3 at pH 7.0 was prepared, and the sample was prepared to a concentration of 1 mg / mL using the mobile phase solution as the solvent. The gel permeation chromatography column temperature was set to 30℃, the pump flow rate to 1 mL / min, and the RID detector temperature to 30℃ before injection. Test instrument: Shimadzu LC-2050C gel permeation chromatography system.

[0112] (4) SEM images were taken of the ceramic coating on the diaphragm surface. ImageJ software was used to capture images of any area of ​​25.6μm × 19.2μm where the effective area of ​​the pores was 0.8μm. 2 ~10μm 2 The number of holes was counted.

[0113] (5) Peel strength: A layer of double-sided tape is pasted on the steel plate, the diaphragm is placed flat and lightly pressed on the double-sided tape, and then a layer of test tape is pasted on the surface of the first area of ​​the diaphragm. The pressure roller (2000g) is held and rolled back and forth on the test tape three times. One end of the tape is torn to the middle of the sample, and the tensile testing machine is used to peel it 180 degrees at a peeling speed of 50mm / min and a peeling test time of 1min. The test tensile strength value is divided by the width of the corresponding tape to obtain the final peel force N / m.

[0114] (6) Moisture content test: The moisture content of the diaphragm is tested using a Karl Fischer AKF-CH6 instrument. The software automatically calculates and displays the moisture content.

[0115] (7) Diaphragm permeability: The diaphragm permeability value was tested using the Xiong Gu Wang Yan Shi 0518-P air permeability meter, which is to evaluate the diaphragm permeability performance by measuring the time required to 100cc of air.

[0116] (8) Heat shrinkage performance test: Cut three 100mm × 100mm square samples from the diaphragm to be tested. Place the samples flat in an oven preheated to the set temperature (150℃) and heat for 1 hour. Remove the samples, allow them to cool at room temperature, and then measure the length of the marked line again.

[0117] Heat shrinkage rate = [(initial length - length after heating) / initial length] × 100%.

[0118] The test results are shown in Tables 1 and 2.

[0119] Table 1 Polymer characterization and performance characterization

[0120] Table 2. Membrane performance characterization

[0121] As can be seen from Tables 1 and 2, all of Examples 1 to 12 can obtain diaphragms with better overall performance.

[0122] In Examples 1-3, Comparative Examples 1, 3, and 4, adjusting the ratio of comonomers, specifically by adjusting the ratio of hydrophilic monomer A and thermosensitive monomer B, alters the LCST temperature and adhesive properties of the binder. Increasing the proportion of thermosensitive monomer B raises the LCST temperature of the binder, thereby reducing the moisture content of the coated film. Due to the characteristics of LCST, the binder forms polymer insolubles during the drying process, creating pores on the membrane surface, which improves the membrane's permeability. Comparative Example 1 uses a binder without thermosensitive monomers, resulting in a membrane with high moisture content and no pores, thus lacking the advantage of good permeability. In Comparative Examples 3 and 4, the amount of thermosensitive monomer was too high and too low, respectively. Insufficient amount of thermosensitive monomer resulted in no obvious LCST characteristics of the binder (as in Comparative Example 4), while excessive amount of thermosensitive monomer resulted in a significant increase in the LCST temperature of the binder. When the temperature of the coating oven was lower than the LCST temperature of the binder, this temperature was insufficient to induce the LCST behavior of the binder. Therefore, it was impossible to achieve low moisture content and it was not conducive to the formation of pores on the membrane surface, thus failing to improve the air permeability of the membrane.

[0123] In Examples 4-5 and Comparative Example 2, with the same total monomer content, more block copolymerization cycles are equivalent to reducing the number of monomers per end-unit. The LCST characteristic of the binder is positively correlated with the number of monomers in the temperature-sensitive end-unit; the more block copolymerization cycles, the lower the LCST of the binder, or even the absence of LCST characteristics (as in Comparative Example 2).

[0124] As can be seen from Examples 3 and 6, N-vinylcaprolactam has a higher temperature-sensitive effect. At the same ratio, its temperature-sensitive temperature is higher, which causes the binder to form polymer insolubles during the drying process, forming pores on the membrane surface, which is beneficial to improving the air permeability of the membrane.

[0125] As can be seen from Examples 7, 8, Comparative Examples 5 and 6, the molecular weight of the binder can be adjusted by changing the amount of chain transfer agent. The higher the molecular weight, the more significant the LCST effect of the binder. If the molecular weight of the binder is too low, it does not have LCST characteristics, and the corresponding bonding effect is also low.

[0126] As can be seen from Examples 3, 9-11, Comparative Examples 7 and 8, the moisture content in the diaphragm can be changed by adjusting the amount of binder in the formulation. As the amount of binder increases, the moisture content of the diaphragm decreases. However, if the amount of binder added is too high, it will cause too many pores in the diaphragm to ensure low moisture performance, but it will not be able to take into account the thermal performance. Furthermore, if the amount of binder is further increased, it will also affect the preparation of the slurry.

[0127] As can be seen from Example 12, the block copolymers formed by free radical polymerization have a wide molecular weight distribution for the same molecular weight, and their LCST characteristics are lower than those of samples with a narrow molecular weight distribution.

[0128] In summary, below the LCST (e.g., during room temperature slurry preparation), the binder provided in this application exhibits excellent hydrophilicity and extended molecular chains, enabling stable dispersion of ceramic particles (such as alumina and boehmite) to form a uniform and stable aqueous coating slurry. During the drying process after coating, when the temperature exceeds the LCST, the hydrogen bonding between the polymer and water weakens sharply, while the hydrophobic interactions of the polymer chains strengthen. The polymer chains undergo dehydration, conformational collapse, and aggregation, precipitating from the water and achieving thermally induced phase separation. After phase separation, the polymer phase forms a dense adhesive network that firmly binds the ceramic particles while simultaneously "squeezing out" most of the water, forming easily evaporable free water. This significantly improves the kinetics and thoroughness of water removal, resulting in a coating with high internal porosity and extremely low residual moisture. This effectively improves the coating drying uniformity, reduces drying shrinkage stress, thereby mitigating or preventing separator edge curling, and ultimately enhancing the electrochemical performance of the battery.

[0129] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. An adhesive, characterized in that, According to molar percentage, the adhesive is obtained by reacting a monomer composition comprising 20% ​​to 49.5% hydrophilic monomer A, 48% to 78% thermosensitive monomer B, and 2% to 2.5% crosslinking monomer C. The minimum critical dissolution temperature (LCST) of the adhesive in aqueous solution is 40°C to 80°C.

2. The adhesive according to claim 1, characterized in that, The binder has a weight-average molecular weight of 200 kDa to 400 kDa; and / or the polymer polydispersity index (PDI) of the binder is 1.25 to 2.

5.

3. The adhesive according to claim 1, characterized in that, The hydrophilic monomer A includes at least one of acrylic acid, ethyl acrylate, acrylamide, N-hydroxymethylacrylamide, hydroxyethyl methacrylate, and polyethylene glycol methacrylate. And / or, the thermosensitive monomer B includes at least one of N-isopropylacrylamide, N-vinylcaprolactam, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, poly(propylene oxide), and poly(ethylene oxide-propylene oxide) blocks; And / or, the crosslinking monomer C includes at least one of N,N'-methylenebisacrylamide, divinylbenzene, and ethylene glycol dimethacrylate.

4. The adhesive according to any one of claims 1 to 3, characterized in that, The adhesive is obtained from a block copolymer and a crosslinking monomer C through a crosslinking reaction. The general structural formula of the block copolymer is A. x B y The molar ratio of the crosslinking monomer C to the total molar ratio of the hydrophilic monomer A and the thermosensitive monomer B used to form the block copolymer is 1:39 to 1:49; wherein, A x Block A of the polymer represents a number-average degree of polymerization of x; Block B y The polymer B-block represents a number-average degree of polymerization y; x and y are independent integers in the range of 20 to 50; Preferably, the block copolymer has 1 to 2 glass transition temperatures.

5. A method for preparing an adhesive as described in any one of claims 1 to 4, characterized in that, The binder is prepared by free radical polymerization or controlled free radical polymerization.

6. The preparation method according to claim 5, characterized in that, The preparation of the adhesive includes: preparing an aqueous solution of hydrophilic monomer A, thermosensitive monomer B, crosslinking monomer C and an initiator; adding a portion of the aqueous solution to a reaction vessel and reacting until the solution viscosity increases; and adding the remaining aqueous solution to the reaction vessel and reacting. Preferably, the initiator includes at least one of sodium persulfate, ammonium persulfate, and potassium persulfate; Preferably, the amount of initiator is 1% to 2% of the total mass of the hydrophilic monomer A, the thermosensitive monomer B, and the crosslinking monomer C.

7. The preparation method according to claim 5, characterized in that, The preparation of the adhesive includes: preparing hydrophilic monomer A into an aqueous solution of monomer A, and preparing thermosensitive monomer B and crosslinking monomer C into aqueous solutions of monomer B and monomer C, respectively. The aqueous solution of monomer A is mixed with the chain transfer agent and the initiator and then added to a reaction vessel to react until the solution viscosity increases; the aqueous solution of monomer B is added to the reaction vessel and reacted, then the aqueous solution of monomer C is added and reacted, and then a chain transfer cleavage agent is added for cleavage. Alternatively, a portion of the aqueous solution of monomer A is mixed with a chain transfer agent and an initiator and added to a reaction vessel to react until the solution viscosity increases; a portion of the aqueous solution of monomer B is added to the reaction vessel and reacted, followed by a portion of the aqueous solution of monomer C and reacted to form a first multiblock copolymer; a portion of the aqueous solution of monomer A is added to the first multiblock copolymer in the above manner and reacted, followed by a portion of the aqueous solution of monomer B and reacted, followed by a portion of the aqueous solution of monomer C and reacted, and so on, repeated multiple times, with a chain cleavage agent added for cleavage.

8. The preparation method according to claim 7, characterized in that, The amount of chain transfer agent added is 0.5% to 1.5% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C; and / or, the amount of initiator is 0.5% to 2% of the total mass of hydrophilic monomer A, thermosensitive monomer B, and crosslinking monomer C; Preferably, the chain transfer agent comprises at least one of dithioesters, trithiocarbonates, and xanthate compounds; Preferably, the dithioesters include at least one of benzyl dithiobenzoate, S-(thiobenzoyl)thioacetic acid, and 2-cyanopropyl-2-yl dithiobenzoate; And / or, the trithiocarbonates include at least one of 2-(dodecylthiothiocarbonylthio)-2-methylpropionic acid and 4-cyano-4-(dodecylthioalkylthiocarbonyl)thioalkylpentanoic acid; And / or, the xanthate compounds include O-ethyl-S-(3-oxobut-2-yl)dithiocarbonate; Preferably, the initiator includes at least one of sodium persulfate, ammonium persulfate, and potassium persulfate.

9. A ceramic-coated diaphragm, characterized in that, The invention includes a base film and an inorganic ceramic coating layer disposed on at least one surface of the base film; the inorganic ceramic coating layer contains the binder according to any one of claims 1 to 8; Preferably, the inorganic ceramic coating layer has pores on its surface and / or inside, wherein the effective area is 0.8 μm. 2 ~10μm 2 The number of holes is 20 to 50; Preferably, the ceramic-coated diaphragm further contains inorganic ceramic particles, and the mass of the binder is 5% to 20% of the mass of the inorganic ceramic particles, more preferably 5% to 15%; Preferably, the moisture content of the ceramic-coated diaphragm does not exceed 1150 ppm.

10. A battery, characterized in that, Including the ceramic-coated diaphragm as described in claim 9; Preferably, the thickness of the ceramic-coated diaphragm is 1 μm to 5 μm.